Pengaruh Panca Cinta dan Environment Ethics terhadap Perilaku Peduli Lingkungan Siswa Sekolah Dasar: (Sebuah Studi Korelasional) - Arif Mahmuda Pohan; Fauzan Hamidi; Muhammad Darwis Dasopang (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This study aims to analyze the influence of Panca Cinta (Five Loves) and Environment Ethics on the Environmental Care Behavior of elementary school students. The research employed a correlational quantitative design with an ex post facto approach. The population consisted of all elementary school students in Batang Lubu Sutam District, with a sample of 250 students from SD Negeri 0805 Tanjung Baru selected using proportional stratified random sampling technique. Data were collected using three scales: Panca Cinta Scale (25 items, α = 0.92), Environment Ethics Scale (20 items, α = 0.89), and Environmental Care Behavior Scale (20 items, α = 0.91). Data analysis utilized multiple regression analysis and path analysis (PLS-SEM) with SmartPLS 4.0. The results indicated that: (1) the level of students’ Panca Cinta was in the moderate category (mean = 3.495); (2) the level of students’ Environment Ethics was in the moderate category (mean = 3.396); (3) the level of students’ Environmental Care Behavior was in the moderate category (mean = 3.287); (4) Panca Cinta had a positive and significant effect on Environmental Care Behavior (β = 0.392; t = 8.143; p < 0.001); (5) Environment Ethics had a positive and significant effect on Environmental Care Behavior (β = 0.348; t = 7.227; p < 0.001); and (6) Panca Cinta and Environment Ethics simultaneously had a positive and significant effect on Environmental Care Behavior (F = 107.834; p < 0.001; R² = 0.465). These findings strengthen the Value-Belief-Norm (VBN) theory by integrating Islamic religious value dimensions through the concept of Panca Cinta as a spiritual foundation in shaping environmental ethics and pro-environmental behavior among elementary school students.